Birth weight and weight at 1 year are independent determinants of bone mass in the seventh decade: the Hertfordshire cohort study. - Dennison, E; Syddall, H; Sayer, A; Gilbody, H; Cooper, C (2005)
Several studies have shown relationships between growth in early life and adult bone mass; in this article, we evaluate the relative contributions of pre- and postnatal factors to bone mass in the seventh decade. A total of 498 eight men and 468 women who were born in Hertfordshire during the period 1931-1939 and still living there were recruited. Detailed birth records were available. Participants attended a clinic where they completed a detailed health questionnaire, before performance of anthropometric measurements and bone densitometry of the proximal femur and lumbar spine (Hologic QDR 4500). Birth weight was associated with bone mineral content in both men (proximal femur: r=0.16, p=0.0003; lumbar spine: r=0.10, p=0.03) and women (proximal femur: r=0.16, p=0.0008; lumbar spine: r=0.11, p=0.03); relationships with bone mineral density were weaker and were significant at the proximal femur in men only (p=0.03). Relationships between weight at 1 y and bone mineral content were even stronger (proximal femur: men r=0.22, p<0.0001; women r=0.14, p=0.002). In men, 18% of the variance in proximal femoral bone area was explained by a model that included birth weight, weight at 1 y, and adult weight, with the relative contributions attributed to each being 2.8, 6.8, and 8.2%, respectively. In women, similar modeling produced figures of 6.7, 4.2, and 3.9% (overall variance of 15% in proximal femoral bone area). Hence, weight at each of these three points in the life course is important in the determination of adult bone mass, with greater contributions of earlier growth to bone size and mineral content than to bone mineral density.